Land-based Financing in Metropolitan Cities in India: The Case of Hyderabad and Mumbai. (May 2016) - Gandhi, Sahil; Phatak, Vidyadhar K.
Major cities in developing countries face infrastructure shortage and inadequate financial outlays to overcome it. One way to raise finances is by leveraging the increasing urban land values using different mechanisms. This article studies the experience of land-based financing in the metropolitan cities of Hyderabad and Mumbai in India. It assesses the performance of various mechanisms implemented by the principal urban local bodies and development authorities in these cities by examining their design, collections and utilisation of revenues from land-based financing mechanisms for infrastructure provision. It finds that although land-based financing contributes substantially to revenues of public bodies, there are issues regarding efficacy of design and legal validity that need to be addressed to make it sustainable. Further, the article finds that to a certain extent, some of the public organisations use revenues from land-based financing for capital expenditure.